Association Between GSTP1 Ile105Val Genetic Polymorphism and Dependency to Heroin and Opium - Rezaei, Majede; Saadat, Mostafa (Biochemical genetics, 2019)
Relationship between glutathione S-transferase P1 ( GSTP1 , OMIM: 134660) variants and the risk of drug dependency is unknown. Chronic use of illegal drugs leads to oxidative stress, which can be alleviated by cellular detoxification mechanisms. There are several polymorphisms in the GSTP1 , including Ile105Val (rs1695). This polymorphism leads to an Ile105Val amino acid change and may alter the GSTP1 enzyme activity. There is no study on the association between this polymorphism and risks of heroin (HD) or opium (OD) dependency. This paper consists of two case–control studies. The first study consisted of 442 HD subjects and 794 healthy controls. The second study consisted of 143 cases with OD and 565 healthy blood donors as controls. Genotyping were carried out using PCR based method. The Ile/Val (OR 0.84, 95% CI 0.65–1.07, P = 0.165) and Val/Val (OR 0.87, 95% CI 0.56–1.36, P = 0.879) genotypes did not show significant association with the risk of HD. Neither the Ile/Val (OR 0.72, 95% CI 0.49–1.06, P = 0.103) nor the Val/Val (OR 0.61, 95% CI 0.29–1.30, P = 0.209) was associated with the risk of OD. The GSTP1 Ile105Val polymorphism was not associated with the risk of dependency to opium and heroin.